Teaching religious studies and theology at Russian universities: problems and tasks from the point of view of teachers of religious studies and theology (based on expert interviews) - Lenkov, Pavel (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2023)
The article is devoted to the study of the teaching of religious studies and theology in the universities of St.Petersburg in the aspect of considering problems and prospects from the point of view of the teachers themselves. The study was conducted in February-March 2022 using a qualitative method, an expert semi-structured interview. The interviewed were determined during the target sample. The selection criteria were as follows: (1) All respondents should be professionally busy as teachers of religious studies and (or) theology at universities in St. Petersburg, (2) temporary criterion-teaching experience at the university for at least 13 years, (3) candidate or doctoral scientific degree. The experts identified the following key problems, related to theology teaching: the problem of personnel training, the lack of a line of textbooks, the insufficient development of the very concept of theology as a subject in higher education, the lack of qualified specialists in Islamic theology, the danger of dogmatization and ideologization in the field of teaching theology. Experts expressed different points of view regarding the very fact of the emergence of theology in secular universities. Some experts noted the preference for a model that implies the interaction and complementarity of theology and religious studies. Secularism, which in the past set the paradigm of religious education exclusively from secular neutral positions, had its costs associated with the dogmatization of the secular approach to the study of religion. In order to overcome these costs, it is desirable that both religious scholars have respect for theology, and theologians for religious studies. As for religious studies, here, according to experts, there is only one area that needs improvement, again, the area of personnel training. One of the questions in guide of the interview was the question of the demand for graduates of such specialties as religious studies and theology. According to all experts, a specialist with a religious and theological education can work as a teacher or researcher, in addition, individual experts indicated that graduates of the relevant specialties can work as school teachers, employees of religious structures and institutions, work in state authorities and local self-governments, and museums.